Current strategies in the farm practices and post-harvest pesticidal defence - Luciano Suss; Fabio Molinari (Italian Journal of Agronomy)
Today, people often talk about biologic agriculture and Integrated Production (IP), even if the real meaning of these terms is altered. In both cases, they deal with production methods characterized by a particular attention to the reduction of the environmental impact of all the farm practices used, especially for defence from adversities, being the element of major concern for environment and consumers’ health.Farm practice evolution, especially those about pest defence, is based on important conceptual change, accurate scientific analysis and organization of technical assistance, rationalization of agri-pharmaceutical product use is one of the main objective of Integrated Production Specifications (IPS). The quantitative reduction is the first objective, obtained by various means such as the use of efficient equipment and the qualitative selection based on the priority use of minor impact means, effectiveness being equal. At post-harvest, the anti-parasitary defence is undergoing deep changes in our country. Once, pesticides very toxic and persistent were used; however, in the last years the availability of active principles (a.p.) usable on foodstuffs or in productive environments; for instance, methyl bromide use has been progressively reduced till its banishment because it is recognized to damage the ozone layer. Thus, on the whole we can talk about “integrated pest management” even for the post-harvest sector. However, substantial differences exist between agriculture and post-harvest, thus the integrated pest management in food production environment has to be designed in a different way. The fundamental element of this technique is to identify a tolerance threshold to pest attack but for the defence of food industries and stored foodstuffs is very difficult, if not impossible, to fix a limit to insect presence after which intervening is compulsory. Monitoring of pest attacks and the implementation of prevention practices is fundamental; in post-harvest sector this activity can be carried out checking first matters to be stored and used by suitable analysis, as well as modifying systems, department structure, installing double door and air blade barriers, laying of pavements with special epoxy paints, replacing the traditional electric raceways with others, totally opened, steel grated, vertical and surely less delicate. As stated above, integrated pest management is a well estabilished technique, even if under continuous refinement; at post-harvest we are in a still transitory phase at the moment. However, industry are making great efforts to give consumers foods protected against pest attacks along the whole productive row, with strict hygienic and safety criteria.